Avaliação do aleitamento materno de lactentes com frênulo lingual duvidoso - Gehm, Camila (2018)
Objective: The aim of this study is to verify, through the Breastfeeding Assessment Protocol, the prevalence of behaviors that indicate feeding difficulties on nursing infants with suspected lingual frenulum. Methods: The sample, observation and assessment of 30 nursing infants, 16 males (53,3%) and 14 females (46,7%), ages ranging from 0 to 3 months which were selected by the hospital Speech Therapy Service due to a suspected lingual frenulum diagnosis. Outcomes: regarding the age, 30% (9) of nursing infants from 0 to 1 month, 53,3% (16) from 1 to 2 months and 16,7% (5) from 2 to 3 months. Regarding the infants position, 13% (4) were not close enough to their mothers’ bodies (ineffective positioning). Regarding the responses to the mother’s breast it was observed a prevalence of 30% (9) of infants who did not latch on to the areola. Regarding the suction it was observed a prevalence of 60% (18) of infants who presented a nearly closed mouth, pouting their lips. Conclusion: Upon analysing the results it can be concluded that nursing infants with suspected lingual frenulum present a greater prevalence of behaviors that indicate feeding difficulties, concerning the “mother’s breast” and “suction”, in the respective items “infant does not latch on to the areola”, “infant with a nearly closed mouth, pouting lips”, “lower lip pointing inwards”, “dimpling of the cheeks” “quick and shallow sucks” was where the greatest difficulties were observed.